Search for direct chargino production in anomaly-mediated supersymmetry breaking models based on a disappearing-track signature in pp collisions at √s = 7 TeV with the ATLAS detector - Alonso, Francisco (2013)
A search for direct chargino production in anomaly-mediated supersymmetry breaking scenarios is performed in pp collisions at √s = 7 TeV using 4.7 fb-1 of data collected with the ATLAS experiment at the LHC. In these models, the lightest chargino is predicted to have a lifetime long enough to be detected in the tracking detectors of collider experiments. This analysis explores such models by searching for chargino decays that result in tracks with few associated hits in the outer region of the tracking system. The transverse-momentum spectrum of candidate tracks is found to be consistent with the expectation from the Standard Model background processes and constraints on chargino properties are obtained.